Manajemen Bandwidth dengan Hierarchical Token Bucket (HTB) untuk Meningkatkan Efisiensi Jaringan Internet - Abdul Azis; Rahman, Miftahur; Daryanto; Henny Wahyu Sulistyo; Hardian Oktavianto; Nur Qodariyah Fitriyah (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2026)
The Semboro District Office has an internet connection of up to 300 Mbps used for public services, employees, and public access. However, the absence of bandwidth management causes unstable connectivity, particularly for service-related devices, reducing service quality. This study implements the Hierarchical Token Bucket (HTB) method to manage network bandwidth. The results indicate that after HTB implementation, each user receives bandwidth according to their assigned profile without exceeding predefined limits. The initial downstream bandwidth of 23.51 Mbps decreased to 18.37 Mbps after implementation. Quality of Service (QoS) evaluation shows a score of 3.75, categorized as good. Throughput increased from 21k to 41k, delay decreased from 46.335 ms to 16.7 ms, and jitter decreased from 0.058 ms to 0.000035 ms, while packet loss remained at 0%. These results conclude that HTB implementation improves network stability.